The effect of grain size on the forces governing the dynamic behavior of electrostatically driven powder media - Salvatierra, Lucas Matías (2013)
The aim of this paper is to identify the forces that govern the dynamic behavior of polydisperse granular systems under high electric fields in air media. In a previous paper, we reported the changes in the morphology and dynamics of grain structures under a frequency and amplitude variable voltage and summarized them in a diagram [L. M. Salvatierra et al., Chem. Phys. Lett. 481, 194 (2009)]. In the present article, we investigate the influence of the grain size distribution and the speed of voltage increase during tests. We explain the main transitions observed in the diagram in terms of the change in grain size and the frequency-dependent electrical response, related to electrophoretic and dielectrophoretic interactions.